Microbial community structures and important taxa across oxygen gradients in the Andaman Sea and eastern Bay of Bengal epipelagic waters - Guo, Ruoyu; Ma, Xiao; Zhang, Jingjing; Liu, Chenggang; Thu, Chit Aung; Win, Tun Naing; Aung, Nyan Lin; Win, Hlaing Swe; Naing, Sanda; Li, Hongliang; Zhou, Feng; Wang, Pengbin (Frontiers in Microbiology, 2022)
In oceanic oxygen minimum zones (OMZs), the abundances of aerobic organisms significantly decrease and energy shifts from higher trophic levels to microorganisms, while the microbial communities become critical drivers of marine biogeochemical cycling activities. However, little is known of the microbial ecology of the Andaman Sea and eastern Bay of Bengal (BoB) OMZs. In the present study, a total of 131 samples which from the Andaman Sea and eastern BoB epipelagic waters were analyzed. The microbial community distribution patterns across oxygen gradients, including oxygenic zones (OZs, dissolved oxygen [DO] ≥ 2 mg/L), oxygen limited zones (OLZs, 0.7 mg/L< DO < 2 mg/L), and OMZs (DO ≤ 0.7 mg/L), were investigated. Mantel tests and Spearman’s correlation analysis revealed that DO was the most important driver of microbial community structures among several environmental factors. Microbial diversity, richness, and evenness were highest in the OLZs and lowest in the OZs. The microbial community compositions of OZ and OMZ waters were significantly different. Random forest analysis revealed 24 bioindicator taxa that differentiated OZ, OLZ, and OMZ water communities. These bioindicator taxa included Burkholderiaceae, HOC36, SAR11 Clade IV, Thioglobaceae, Nitrospinaceae, SAR86, and UBA10353. Further, co-occurrence network analysis revealed that SAR202, AEGEAN-169, UBA10353, SAR406, and Rhodobacteraceae were keystone taxa among the entire interaction network of the microbial communities. Functional prediction further indicated that the relative abundances of microbial populations involved in nitrogen and sulfur cycling were higher in OMZs. Several microbial taxa, including the Thioglobaceae, Nitrospinaceae, SAR202, SAR406, WPS-2, UBA10353, and Woeseiaceae, may be involved in nitrogen and/or sulfur cycling, while also contributing to oxygen consumption in these waters. This study consequently provides new insights into the microbial community structures and potentially important taxa that contribute to oxygen consumption in the Andaman Sea and eastern BoB OMZ.